Analisis faktor -faktor yang mempengaruhi keputusan investasi reksa dana pada masyarakat di Indonesia - Fadhiilah, Annis (Economics, Finance, and Business Review, 2025)
Mutual funds are a capital market investment instrument that manages investor funds through investment managers. This study was conducted to determine the internal and external factors of individuals that influence decision-making to invest in mutual funds. The data used in this study are primary data processed using data analysis methods, namely Structured Equation Modeling-Partial Least Square (SEM) with Smart PLS 3 software. The results of the study indicate that financial literacy, minimum investment capital, investment returns, and subjective norms have a positive influence on mutual fund investment decisions. The better the financial literacy, the cheaper the minimum investment capital, the higher the investment returns, and the higher the subjective norms a person has will increase people’s decisions to invest in mutual funds. The implications of this study from the government’s side need to improve financial literacy to increase the capacity and quantity of investment in mutual funds. From the mutual fund company’s side, it is necessary to take into account returns and provisions such as minimum capital to attract people to invest.